The Role of Play in Developing Children's Social and Emotional Skills - Kandi kandi (Pt. Anagata Sembagi Education, 2026)
Children's social and emotional development forms a critical foundation for their readiness to face future life challenges, whether in academic settings, interpersonal relationships, or adaptation to a dynamic social environment. Play encompassing both traditional and modern forms has proven to be one of the most effective strategies for supporting this development. Beyond serving as a source of entertainment, play carries an educational dimension that stimulates children to share, cooperate, empathize, regulate their emotions, and understand social rules. This study aims to explore in depth the role of play in shaping children's social and emotional skills through an SIR (Study, Interpretation, and Reflection) approach. The findings show that play contributes significantly to building interaction and communication skills, emotional regulation, and conflict-resolution ability. This article is expected to offer a scholarly contribution for educators, parents, and other stakeholders in designing learning strategies that are more inclusive and enjoyable, enabling children to develop holistically through play